Forged Letters: Counterfeit Manumission Certificates and Subaltern Writing Practices as Used by Enslaved Individuals in Early Modern Iberia - Fernando Bouza (Journal of Early Modern Studies)
The focus of the essay is the fabrication, circulation and use of ‘forged documents’ by subaltern groups, and in particular, counterfeit manumission certificates created for and by enslaved individuals in Iberia during the sixteenth and seventeenth centuries. The analysis of ‘forged documents’ provides a deeper insight into how official model documents were appropriated by these subaltern illiterate groups. Furthermore, it provides a testimony of the dynamics of subaltern responses to documentary norms and models along the lines discussed by Donald F. McKenzie.